STRATEGI PENGEMBANGAN PROGRAM PERTANIAN TANAMAN PANGAN PADA EMPAT KAMPUNG DI DISTRIK SEMANGGA KABUPATEN MERAUKE - Andri Prasetyo; Untari Untari (Universitas Musamus, Merauke, Papua, 2011)
The research objective is to analyze the influence of factors of production and farm income on rice and corn crops. The study was conducted in the District Semangga, Merauke Regency, Papua Province. The reaserch method used is descriptive analitycal method, with 47 respondentsin the sample taken at random sample. Data were analyzed with analysis of farm and cron crops Cobb-Duglas Function. Based on the research results can be concluded that the factors of production that significantly affect the production of rice seed production is a factor of 68,2%, and fertilizer production factor of 34,6%. While the factors of production that do not significantly affect the production factor labor by factor of 13,4% and pesticides production by 0,4%. On farm corn production factors that significantly affect seed production is a factor of 84,7%, and pesticides factor of 15,2%. While the fertilizer factor of 11,6% and employment by 5,8% did not significantly affect the production of corn farming. Revenues for the farming of corn is greater than the income rice farming. Corn farmers who are farming income is Rp. 25.847.097.40 and rice farming is Rp. 6.449.494.40. when farmers are seeking the two together in a single family income of Rp. 32.296.591.80 during the planting period.